MEDICINAL PLANTS GROWN IN SOIL AMENDED WITH STRUVITE RECOVERED FROM ANAEROBICALLY PRETREATED POULTRY MANURE WASTEWATER - K. Yetilmezsoy; F. I. Turkdogan; A. Gunay; T. Yilmaz; M. Kaleli (Journal of Animal and Plant Sciences, 2013)
Struvite (magnesium ammonium phosphate hexahydrate, MgNH4PO4.6H2O, MAP) recovered from up-flow anaerobic sludge blanket (UASB) pretreated poultry manure wastewater (MgCl2.6H2O + KH2PO4, Mg2+:NH4+ -N:PO4 3- -P = 1:1:1, pH = 9.0) was tested as a slow release fertilizer on the growth of four medicinal plants including garden rocket (Eruca sativa), dill (Anethum graveolens), fennel (Foeniculum vulgare) and parsley (Petroselinum crispum) in a series of lab- scale greenhouse experiment. Pot trial tests indicated that rates of increase in fresh weights, dry weights and fresh heights of plants grown in soil fertilized with the recovered struvite were determined as 405%, 488%, and 51% for garden rocket; 154%, 191%, and 44% for dill; 152%, 379%, and 27% for fennel; 141%, 208%, and 22% for parsley, respectively, compared to the control pot. Results of a static bioassay test proved that the use of plants cultivated in MAP pots as the feeding material did not cause any acute toxicity symptoms or mortality in guppy fish (Lebistes reticulatus), and all survived and exhibited normal visual responses at the end of 170-h exposure. Findings of this study confirmed that the recovered struvite from UASB effluent provided a valuable slow release fertilizer for the agricultural use, resulting an edible multi-nutrient animal feed.
Keywords: Poultry manure wastewater; up-flow anaerobic sludge blanket; magnesium ammonium phosphate; medicinal plants; fertilizer; acute toxicity